Peripheral neuropathies after bariatric surgery. Preliminary results from a single-centre prospective study in Northern Italy. - Riccò, Matteo; Rapacchi, Chiara; Romboli, Andrea; Vezzosi, Luigi; Rubichi, Francesco; Petracca, Gabriele Luciano; Ferrari, Stefania; Valente, Marina; Tartamella, Francesco; Marchesi, Federico (Acta Biomedica Atenei Parmensis, 2019)
Introduction: Bariatric surgery (BS) has gained popularity in order to treat morbid obesity. However, post-operative (PO) neurologic complications have become increasingly recognized. Our aim was to examine incidence, clinical presentation, and outcomes of neurologic disorders secondary to BS. Methods: Patients who underwent BS between the years 2012 and 2015 at Parma University were included in this survey, and assessed before (T0) and 1 year after surgery (T1). Baseline characteristics and medical comorbidities, type of surgery, and PO complications were retrieved. Patients with a previous history of peripheral neuropathic disease were excluded from the analysis. If a patient presented with a new onset neurologic symptom including extremity numbness, paresthesia, muscle weakness, the status was considered “positive” for PO-neuropathy. Results: Overall, we retrieved data from 61 patients (n=30 Roux-en-Y Gastric bypasses, n=31 Gastric banding; 81.0% females). Of them, 7 (11.4%) developed some signs of PO-neuropathy, that eventually disappeared at T+24 months. The most common manifestations were paresthesia (n=6) and muscle weakness (n=4), similarly distributed in Gastric Bypass (n=4) and Gastric Banding (n=3) groups. Although patients affected by PO-neuropathy exhibited higher SF-36 score at T0 (p=0.018), no significant differences were found regarding BMI (T0, T1), percentual weight loss, serological data (i.e. vitamin B1, B2, B6, B12: in all cases p>0.05). Conclusion: PO-BS neuropathy is usually associated with lower levels of vitamin B1, B2, B12. However, no differences in PO-BMI, excess weight loss, and metabolic data levels were found. Larger data and more extended follow-up are required to validate our results.